Interação solo-estrutura de edifícios com fundações superficiais - Antoniazzi, Juliana Pippi (2011)
This work deals with the consideration of Soil-Structure Interaction (SSI) in structural design of reinforced concrete buildings on shallow foundations of the isolated footing type. It carried out a comprehensive review on the major works done in the area and the methods for obtaining parameters and variables involved in the analysis. Numerical examples were developed with the aim of identifying internal forces and displacements changes caused by considering the deformation of soil and the construction sequence in the structural analysis. The examples also intended to show data and procedures for the required calculations in the consideration of the SSI in structural designs. Among the computational tools used in the numerical examples is ESPACIAL_ISE program - a program developed in FORTRAN by Alva (2010). This program employs the method of Aoki and Lopes (1975), which uses the equations of Mindlin (1936) for calculating the settlements, together with the Steinbrenner´s method (1934) to consider the stratigraphy of the soil mass. It was also used in the numerical examples SISEs computer system (System of Soil-Structure Interaction) - developed by TQS Informatics - which allows that the entire structure and foundation are represented in a single structural model. The results of this study showed the importance of considering the soil deformation, although in a simplified form, replacing the fixed support hypothesis in structural designs. Thus, for a more realistic structural analysis of multistory buildings, it is recommended that the soil-structure interaction is considered together with the construction sequence.